Gomes Casseres, creador de postales fotográficas en Costa Rica (1907-1920) - Enrique Camacho Navarro (L'Ordinaire des Amériques)
During the first half of the twentieth century, the United Fruit Company (UFCo.), a multinational corporation founded in 1899 in order to exploit the agricultural wealth of the Caribbean, was responsible for considerable amounts of propaganda, newspaper ads, postcards, books, etc. These were linked to the commercial and tourism activities of the United States in Caribbean countries. The goal of UFCo was to influence the imperial vision of the Central American and Caribbean area from an iconographic point of view. In that world of images, postcards were very important as artifacts in which a visual discourse imposed an ideal of social imagination that was stimulated by the banana company. One of the artists who participated in this process was Gomes Casseres, a photographer who left his name printed on several postcards that have been found and have been subjected to iconological examination. This paper will analyze such cultural artifacts and will show that these images responded to the idea of Caribbean geography that "mamita yunai" constructed and which imposed itself from afar as the "reality" of Costa Rica.